2010
DOI: 10.2215/cjn.00740110
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Biomarkers in the Clinical Prognosis and Early Detection of Acute Kidney Injury

Abstract: Background and objectives: Several novel urinary biomarkers have shown promise in the early detection and diagnostic evaluation of acute kidney injury (AKI). Clinicians have limited tools to determine which patients will progress to more severe forms of AKI at the time of serum creatinine increase. The diagnostic and prognostic utility of novel and traditional AKI biomarkers was evaluated during a prospective study of 123 adults undergoing cardiac surgery.Design, setting, participants, & measurements: Urinary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
255
1
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 322 publications
(276 citation statements)
references
References 47 publications
13
255
1
7
Order By: Relevance
“…Koyner et al (29) found that urine NGAL soon after arrival into the ICU after cardiac surgery accurately predicted the development of stage 3 AKI and that preoperative urine KIM-1 levels were moderately predictive. Parikh et al (30) For risk classification, predicted primary outcome occurrence (increased AKI stage from enrollment to peak creatinine, need for dialysis or in-hospital death) of Ͻ20%, 20 to 40%, and Ͼ40% was considered low, intermediate, and high risk, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Koyner et al (29) found that urine NGAL soon after arrival into the ICU after cardiac surgery accurately predicted the development of stage 3 AKI and that preoperative urine KIM-1 levels were moderately predictive. Parikh et al (30) For risk classification, predicted primary outcome occurrence (increased AKI stage from enrollment to peak creatinine, need for dialysis or in-hospital death) of Ͻ20%, 20 to 40%, and Ͼ40% was considered low, intermediate, and high risk, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with ADHF, fluid retention, low protein intake, and decreased creatinine production secondary to muscle atrophy may dissociate creatinine levels from reflecting the true severity of renal dysfunction. Diagnostic mainstays such as the fractional excretion of sodium and urea have been shown to be suboptimal in a variety of clinical settings (13)(14)(15)(16)(17). Assessment of biomarkers for renal tubular injury (e.g., neutrophil gelatinase-associated lipocalin [NGAL], kidney injury molecule-1 [KIM-1] and IL-18) at the time of creatinine-based diagnosis of AKI offers prognostic information in multiple clinical settings such as cardiac surgery, ICU, transplantation, and cirrhosis (18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…As described above, baseline renal function has been shown to impact a biomarker's ability to detect AKI in a variety of clinical settings (35,46). However, for several biomarkers, some clinical variables, outside of renal function, have been shown to impact biomarker concentrations and affect their ability to detect clinical end points.…”
Section: Biomarkers In the Setting Of Critical Illness And Sepsismentioning
confidence: 99%
“…Each individual type of AKI has its own distinct pathophysiologic (and biomarker) fingerprint; for example, the biomarkers that diagnose and prognosticate ischemia-reperfusion AKI may be different from those biomarkers that detect sepsis-associated AKI or those biomarkers that forecast radio contrastassociated AKI. Similarly, every biomarker has its own distinctive kinetics, and accordingly, certain individual biomarkers may excel in detecting early AKI, whereas others may help prognosticate outcomes at the time of creatinine elevation (46). To date, several individual biomarkers have excelled at detecting multiple aspects of AKI in the setting of both cardiac surgery and critical illness.…”
Section: Summationmentioning
confidence: 99%